Reactions of o,o′-Dihydroxy Azo Dyes with the Third Group M(III) Ions: A Spectroscopic and Electrochemical Study - Solomiya Pysarevska; Liliya Dubenska; Ivan Spanik; Jaroslav Kovalyshyn; Sofia Tvorynska (Journal of Chemistry)
The reactions of some metal ions of the third group (M(III)) with azo dyes were studied. Attention was focused on azo dyes with two hydroxy groups in ortho-positions to azo group: eriochrome red B (ERB), eriochrome black T (EBT), eriochrome blue SE (EBSE), calcon (Calc), and kalces (KLC). The chelation is responsible for interaction of these dyes with Al(III), Sc(III), rare earth elements (REE) ions, Ga(III), and In(III). The complexes were studied using vis- and IR-spectrometry. One irreversible peak (P1) of complexes reduction was observed on voltammograms for all studied metal ions. The second peak P2 was observed only for Ga complexes with all investigated azo dyes. Based on the study, the possible mechanism of complexes reduction was proposed. Linear behavior has been found between the reduction peak currents of a set of metal complexes and the concentration of the respective metal cations. This can be used for metal ions determination by voltammetric methods.